ANALYSIS OF INTERNAL CONTROL EFFECTIVENESS OF INDIHOME SALES SYSTEM AND CASH RECEIPTS AT PT. TELECOMMUNICATION INDONESIA REGIONAL 5 JATIM BALNUS - Alvionita, Fina; Pratiwi, Yana Eka; Lastiani, Siwidyah Desi (JEA17: Jurnal Ekonomi Akuntansi, 2024)
The purpose of this study was to determine the effectiveness of internal control on the IndiHome sales system and on the cash receipt system at PT Telekomunikasi Indonesia Regional 5 Jatim Balnus. The research method used is a qualitative method with primary and secondary data collection techniques, primary data collection using interview techniques obtained from resource persons of PT. Telkom Regional 5 Jatim Balnus. The research object used is the internal control procedures for IndiHome sales and cash receipts. This study analyzes several factors regarding the application of internal control effectiveness in accordance with the components of internal control according to COSO which includes five components, namely the control environment, risk assessment, control activities, information and communication, and monitoring. The result of this study is the implementation of the effectiveness of internal control over the IndiHome sales system and cash receipts at PT. Telekomunikasi Indonesia Regional 5 Jatim Balnus has been running in accordance with applicable procedures in accordance with company rules.